PHENOTYPIC AND GENOTYPIC CHARACTERIZATION OF FLUOROQUINOLONE DRUG RESISTANCE AMONG STAPHYLOCOCCUS AUREUS IN A TERTIARY CARE HOSPITAL - NAMEIRAKPAM, SHELINA; SSM, UMA MAGESWARI; M, KALYANI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to determine whether recent use of topical fluoroquinolones is a risk factor for in vitro fluoroquinolone resistance in Staphylococcus aureus ocular isolates. Fluoroquinolone antibiotics such as ciprofloxacin (CIP) are useful drugs against infections caused by Staphylococcus aureus and mutations in deoxyribonucleic acid (DNA) gyrase which control bacterial DNA topology, can be one of the reasons of occurrence resistance to this class of antibiotics. Therefore, finding new mutations and study of the quinolone interaction with mutated GyrA can provide important issues for explanation resistance. Methods: Bacterial identification was confirmed by appropriate morphological, cultural, and biochemical tests. The antibiotic susceptibility pattern was determined for all isolates. The possible involvement of efflux pumps in mediating fluoroquinolone resistance as well as changes in the quinolone resistance-determining region (QRDR) of gyrA gene was investigated. Results: Differences in methicillin resistance among staphylococci were observed based on patient age, with higher rates observed in older patients (p<0.0001). Out of 91 isolates, 77 (84.61%) were resistant to CIP and 47 (51.65%) were resistant to ofloxacin (OF). Confirmation with agar dilution test showed that 57 samples were resistant to CIP, 38 samples were resistant to OF, and 29 samples were resistant to both CIP and OF. By polymerase chain reaction (PCR) testing, gyrA genes in resistance strains were amplified. All the five resistant isolates were found to be positive for the presence of a fluoroquinolones resistance gene (gyrA gene) and the two sensitive isolates were found to be negative. Resistance among CIP and OF in isolated harboring a mutation GyrA was of statistical significance among S. aureus (p<0.001). Conclusion: The result of this study will be useful to update the antibiotic policy in our hospital set up and controlling the irrational use of antibiotics among health care workers. The information obtained will provide a baseline data that can be used to design further research for prevention of drug resistance caused by Staphylococcus aureus.